Pengaruh Kepemilikan Saham terhadap Manajemen Laba dengan Profitabilitas sebagai Moderasi - Rizky Huzaefa; Vinola Herawaty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to examine the influence of share ownership on earnings management practices by considering profitability as a moderating variable. The research method used includes quantitative data analysis from the financial statements of publicly listed companies on the stock exchange, where the data is systematically collected and meticulously analyzed. There are 214 samples used in this study, selected based on certain criteria to ensure the representativeness of the samples. The results of the study are expected to make a significant contribution to the literature on earnings management and provide practical insights for stakeholders, including investors and regulators, in understanding the dynamics between share ownership, profitability, and earnings management.